The pre-trial investigation of corruption crimes - Dekailo , Petro; Shpylyk , Yuliia (Actual problems of law (Aktual’ni problemi pravoznavstva), 2025)
This paper focuses on the study of pre-trial investigations of corruption crimes. The significance of this research stems from the crucial role pre-trial investigations play in the fight against corruption, a pervasive threat undermining societal trust and economic stability. A thorough understanding of the procedural aspects of pre-trial investigation – including its commencement, jurisdiction determination, the execution of investigative actions (both overt and covert), special pre-trial investigation procedures, suspension, and termination – is paramount for effective application in practice. This in-depth study is vital for equipping future law enforcement officers, lawyers, and other legal professionals with the knowledge necessary for the correct implementation and application of relevant legal provisions. Corruption, a cancer on the body politic, erodes public trust, distorts markets, and diverts resources away from essential public services. Its insidious nature allows it to flourish in the shadows, requiring robust and efficient pre-trial investigative mechanisms to uncover and prosecute offenders. The complexity of corruption cases necessitates a comprehensive understanding of the legal framework governing pre-trial investigations to ensure thoroughness, fairness, and ultimately, justice. Therefore, a detailed examination of the pre-trial investigation process is not simply an academic exercise, but a crucial component in combating the devastating effects of corruption on society. The practical application of this knowledge is critical for achieving effective prosecution and deterrence. The conclusions state that by acting within the framework of the CPC, pre-trial investigation bodies ensure one of the most important principles – legality, and thus the rule of law. Evidence collected in violation of criminal procedural law is declared inadmissible by the court, and thus helps to avoid criminal liability of perpetrators of corruption crimes, which leads to their impunity and undermines confidence in the legal system of the state. Thus, unconditional compliance with the CPC at the pre-trial investigation stage is a key factor in the successful fight against corruption and ensuring justice.